Tuberculosis: Primary Diagnosis From an Oral Ulcer - Rodrigues, Bruno Teixeira Gonçalves; Guimarães, Alexandre de Freitas Caetano; Pires, Fábio Ramôa; Israel, Mônica Simões (Journal of Oral Diagnosis, 2020)
Tuberculosis (TB) is a contagious chronic disease caused by Mycobacterium tuberculo- sis. Tuberculosis can manifest within the oral cavity as a painless chronic ulcer - which resembles several other oral diseases - at this moment, diagnosis can be achieved through an incisional biopsy. We report a case of TB diagnosed from an oral ulcer in a 54-year- -old male referred for evaluation of a 1-month lasting non-healing ulcer in the tongue. Intraoral clinical examination revealed a single painless chronic ulcer with irregular borders located in the apex of the tongue. Squamous cell carcinoma was the main clinical diagnosis; however, after performing an incisional biopsy and histopathological exami- nation, TB was suggested, and confirmed through the purified protein derivative (PPD) skin test. Patient was then referred to a medical service and confirmed lung involvement by the disease, starting the treatment protocol for TB. A 1-month follow-up showed complete regression of the oral lesion. The patient completed the TB treatment and is under clinical follow-up for 2 years.